Pengaruh Lokasi dan Media Sosial sebagai Bentuk Promosi terhadap Keputusan Pembelian pada Kopi Uwak - Pratiwi, Yunita Dwi; Nurlenawati, Netti; Triadinda, Dexi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to explain the effect of location and promotion through Instagram social media on purchasing decisions both partially and simultaneously using quantitative analysis methods with a verification descriptive research type. Determination of the number of samples using the Cochran formula with sampling techniques using purposive sampling. Collecting data using a questionnaire and analysis using multiple linear regression with SPSS27 software. The results showed 1) Location for Uwak Coffee consumers obtained very good criteria 2) Promotion through Instagram social media for Uwak Coffee consumers obtained very good criteria 3) Purchase decisions for Uwak Coffee consumers obtained good criteria 4) Location partially had positive and significant effects on purchasing decisions of Uwak Coffee 5) Promotion through Instagram social media has a positive and significant effect on purchasing decisions of Uwak Coffee 6) Location and promotion through Instagram social media simultaneously have a positive and significant effect on purchasing decisions of Uwak Coffee with a value of 27.1%.